Inhalable particulate systems for anti-tubercular drug delivery - Nkanga, Christian Isalomboto (Rhodes University, Faculty of Science, Department of Chemistry, 2017)
Tuberculosis (TB) is a deadly infectious microbial disease that is currently dominating public health concerns. Among the pharmacological issues in the management of TB are the poor bioavailability of some anti-TB drugs, mostly due to the fast first-pass metabolism, and high drug load needed for combination therapy. These result in a lengthy treatment with several adverse effects causing decreased patient compliance. These factors often lead to the therapeutic failure and promote the development of drug resistant strains, justifying the urgent need for new therapeutic strategies. Liposomes are lipid-based particulate vehicles known to be the most clinically appointed drug carriers currently. Liposomal systems are reported to be rapidly engulfed by macrophages - where the mycobacterium often resides. This makes liposomes appropriate vehicles for targeted anti-TB drug delivery. Many research groups have reported the potential of liposomes systems to deliver anti-TB drugs. However, the costly formulation status of liposomes, due the use of expensive synthetic or highly purified natural phospholipids, is a limitation to the treatment of a poverty related infectious disease like TB. The aim of this study was to design and develop liposomes for pulmonary delivery of anti-TB drugs using crude soybean lecithin (CL) and its purirified version. CL is an FDA- approved naturally occurring phospholipid mixture that is quite cheap and readily available. Various liposome batches were prepared using a film hydration method and characterized by dynamic light scattering (DLS) and transmission electron microscopy (TEM). Liposomes composed of CL and cholesterol (Chol) in a 3:1 mass ratio were selected for drug encapsulation based on the following characteristics: polydispersity index (PDI, 0.28), mean particles sizes (PS, 502 nm) and zeta potential (ZP, -56 mV). Isoniazid (INH) was encapsulated as a model drug using a freeze-thaw loading technique and an HPLC method was validated for quantitative analysis. The physicochemical properties of INH-loaded liposomes were comprehensively investigated using thermal, microscopy and spectroscopic techniques. This formulation showed a high encapsulation efficiency (%EE) of 78%, much better than the liposomes made from purified lecithin, 20%. Other characteristics of INH- loaded liposomes, which make them attractive for pulmonary TB therapy, are presented in this dissertation. These include a controlled release of 50% of the encapsulated INH over 12 hours. Finally, rifampicin (RIF) was added as a hydrophobic model drug and several evaluations were conducted on these dual drug-loaded liposomes. Of particular interest, it was noted that the dual drug-loaded liposomes made of CL alone showed the highest %EE (59% for INH and 90% for RIF) compared to those containing Chol or those made of purified lecithin. Surprisingly, the average PS of the dual CL-based liposomes (1114 nm) was in the size range reported for optimum deep lung deposition and macrophage uptake. In addition, the mean ZP of these liposomes (-63 mV) seems to be favourable for their shelf stability and internalization by macrophages. Overall, these findings show that the dual CL-based liposomes developed would be promising for macrophage-targeting pulmonary delivery of anti-TB drugs.
Keywords: Uncatalogued